Searching MEDLINE for Aboriginal and Torres Strait Islander health literature: questionable sensitivity. (16th February 2013) - Sladek, Ruth M.; Tieman, Jennifer J.; Tyndall, Jess; Phillips, Paddy A.
Abstract Objective The extent to which existing and future research can impact on reducing health disparities relates not only to the evidence available, but the ability to find that evidence. Our objective is to quantify experts' literature searching effectiveness with respect to Aboriginal and Torres Strait Islander people's health. Methods Nine journals were dual reviewed, and a 'gold standard' set of relevant articles was identified. Health librarians (n = 25) completed a standardised searching task using OVID MEDLINE, and results were compared with the gold standard. Sensitivity, specificity and precision rates were calculated. Results The gold standard comprised 136 of 1469 (9.3%) records from nine journals. Searches achieved a mean sensitivity of 53.2% (median = 64.7%, range 0.0–93.4%), specificity of 97.4% (median = 99.4%, range 52.6–100%) and precision of 83.3% (median = 91.0%, range 16.7–100%). Self‐estimates of search sensitivity (post hoc) were significantly higher than observed (M = 78.9%, t = 4.812, P < 0.001). Conclusions Even expert searchers struggle to find the relevant peer‐reviewed literature in MEDLINE. Implications A search filter may improve searching effectiveness for Aboriginal and Torres Strait Islander health literature. Assessment of health librarians' searching competencies warrants further professional debate and consideration.